Local Structure and Coordination Define Adsorption in a Model Ir1/Fe3O4 Single‐Atom Catalyst. Issue 39 (19th August 2019) - Jakub, Zdenek; Hulva, Jan; Meier, Matthias; Bliem, Roland; Kraushofer, Florian; Setvin, Martin; Schmid, Michael; Diebold, Ulrike; Franchini, Cesare; Parkinson, Gareth S.
Abstract: Single‐atom catalysts (SACs) bridge homo‐ and heterogeneous catalysis because the active site is a metal atom coordinated to surface ligands. The local binding environment of the atom should thus strongly influence how reactants adsorb. Now, atomically resolved scanning‐probe microscopy, X‐ray photoelectron spectroscopy, temperature‐programmed desorption, and DFT are used to study how CO binds at different Ir1 sites on a precisely defined Fe3 O4 (001) support. The two‐ and five‐fold‐coordinated Ir adatoms bind CO more strongly than metallic Ir, and adopt structures consistent with square‐planar Ir I and octahedral Ir III complexes, respectively. Ir incorporates into the subsurface already at 450 K, becoming inactive for adsorption. Above 900 K, the Ir adatoms agglomerate to form nanoparticles encapsulated by iron oxide. These results demonstrate the link between SAC systems and coordination complexes, and that incorporation into the support is an important deactivation mechanism. Abstract : The coordination of a single atom to the oxide support has dramatic consequences on its ability to adsorb carbon monoxide. The observed motifs can be rationalized using simple arguments from coordination chemistry, confirming the hypothesis that single‐atom catalysts have much in common with organometallic complexes used in homogeneous catalysis.